The effect on home advantage when a team changes from grass to artificial turf - a worldwide study in professional football - Diniz da Silva, C.; Paschoal Braga, C.; Pollard, R. (International Journal of Performance Analysis in Sport, 2018)
The use of artificial turf (AT) for professional soccer has been a controversial topic since its introduction in the 1980s. One concern has been its potential to give teams with AT an additional home advantage (HA). After identifying all teams in the top two levels of domestic competition adopting AT after July 2004, the implementation date for FIFA-approved AT, the purpose of the study was to establish whether or not HA for these teams increased as a result of the switch to AT. Only teams playing two seasons on natural turf (NT), followed by two on AT were included, resulting in 43 teams from 13 different countries. A general linear model was fitted, with HA as the dependent variable, with the season as a factor, while controlling for team ability, overall league HA, number of other teams in the league with AT and concomitant switching to a new stadium, all variables that might have had a confounding influence on HA. No significant difference in HA was found between the four seasons (p = .85). This result, together with studies showing no injury, physical or performance difference between AT and NT, gives further validation to FIFA in its current promotion of AT.